Teacher careers and professional dispositions in a diversified school market (Sociologisk Forskning, 2022)
The marketization of the Swedish school system in the early 1990’s has led to an increased social segregation and organizational and pedagogical diversification, in terms of profiling, of Swedish schools. These differences are growing more visible and important for the teachers’ labour market since the teachers synchronise and incorporate professional dispositions and skills of only local validity and therefore only work in limited sectors of the school market. Thus, what seems like an extension of possibilities, through more diverse options, has transformed into a narrower and possibly more segregated labour market.
Keywords: professional disposition; school market; school profiling; school segregation; teacher careers